Ambientes de aprendizaje y su repercusión en el desarrollo socio-cognitivo en los estudiantes de 5to E.G.B de la Unidad Educativa Emigdio Esparza Moreno, 2023 - Castillo Bone, Neyser Rodi (2023)
The (Ministry of Education, 2023) provides teachers and other actors of basic secondary education with a curriculum that allows them to manage the teaching and learning processes at this educational level. The present project will focus its study, due to the fact that most of the middle basic education centers do not have learning environments properly equipped with the necessary materials so that the actions of the educational work can be developed in an optimal way. The problem is centered on the way learning environments have consequences on the socio-cognitive development of students in the fifth year of basic education. In addition, it was found that the absence of educational materials intended for education causes low participation in learning, inadequate performance and low academic achievement. In the survey applied to the students it was evidenced that there is a correlation because the students like the learning corners that the teacher creates and if they participate, but the problem of the students is reflected in the problem that they present when speaking and memorizing and they are very distracted in class, because they do not have a good socio-cognitive development, therefore it is important to help them with the activities so that they can demonstrate their skills. This research is important because it encourages teachers to use cognitive strategies that motivate and awaken in students fundamental factors such as attention, memory and perception, so that in this way they can develop and strengthen students' learning abilities.